2010
DOI: 10.1111/j.1365-2621.2010.02315.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on the amino acid content of New Zealand spinach (Tetragonia tetragonioides Pall. Kuntze)

Abstract: The aim of this work was to evaluate the effect of processing on the amino acid content and protein quality of New Zealand spinach (Tetragonia tetragonioides Pall. Kuntze). In this research, fresh and cooked New Zealand spinach as well as two frozen products prepared for consumption, one obtained using the traditional method (blanching-freezing-storage-cooking) and the other a convenience food product obtained using a modified process (cooking-freezing-storage-defrosting and heating in a microwave oven), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The amino acid content in any given species of raw vegetable depends on such factors as cultivar, usable part and stage of maturity 17, 18. The kale leaves investigated contained more total amino acids than spinach, cauliflower or broccoli 19–21. The mean total content of amino acids in raw kale leaves was 32.41 g kg −1 raw matter, with essential amino acids constituting 44% of the total.…”
Section: Resultsmentioning
confidence: 95%
“…The amino acid content in any given species of raw vegetable depends on such factors as cultivar, usable part and stage of maturity 17, 18. The kale leaves investigated contained more total amino acids than spinach, cauliflower or broccoli 19–21. The mean total content of amino acids in raw kale leaves was 32.41 g kg −1 raw matter, with essential amino acids constituting 44% of the total.…”
Section: Resultsmentioning
confidence: 95%
“…From these findings it may be suggested that the sterilization with electrical method versus retort sterilization is a convenient method to maintain the total amino acids profile in vegetable baby purees. No effects or even increase in amino acid content have also been exhibited in green cauliflower (with the exception of tyrosine) (Slupski, Lisiewska, Kmiecik, Gebcznski, & Sobczynska, 2010a) and in spinach (with the exception of cistine and methionine) (Slupski, Achrem-Achremowicz, Lisiewska, & Korus, 2010b) after culinary process as compared with the composition in raw samples.…”
Section: Resultsmentioning
confidence: 99%
“…These reactions can lead to the formation of new compounds or to the oxidation of minerals, which can reduce the amount of ash [ 20 ]. Słupski et al [ 68 ] reported that technological and culinary processing caused a significant increase in protein content. During evaporation, food products can lose excess water.…”
Section: Discussionmentioning
confidence: 99%